Condition monitoring thermal properties of a 20A hydraulic-magnetic MCB - Roderick Thomas (Proceedings of the 31st International Congress and Exhibition on Condition Monitoring and Diagnostic Engineering Management (COMADEM), 2018)
Condition monitoring of engineering assets as part of a predictive maintenance programme. This paper deals with the technical aspects of electrical based condition monitoring using non-contact infrared thermography technologyHeat is one of the major causes of degradation which can cause a reduction in performance, reliability and life span of miniature circuit breakers (MCBs). In order to diagnose the condition of electrical equipment, the thermal stress of that equipment should be known. The aim of this paper is to use a lumped model and compare with empirical infrared thermographic results relating to the condition of MCBs and to:Define the MCB surface heat distribution after a number of switching operations at rated current.To determine whether the frontal surface temperature of the MCB is an accurate indicator of internal degradation.Determine a field methodology to determine degradation and to anticipate failure of MCBs?